IMPLEMENTASI QUANTUM LEARNING BERBANTUAN MEDIA KARTU LIPAT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPS DI SMP NEGERI 1 BATANG - Sudiami, Dinok; Nisa, Aisyah Nur Sayidatun (HARMONY, 2019)
The problems that arise in a social studies learning at SMP Negeri 1 Batang begin with the use of models and teachers in their teaching learning activities use media learning that. The scientific model has been carried out, but the students remain silent, they do not dare to express their opinions. The teacher had made improvements to make their students to be more active and to increase their outcome learning. The learning model that is used by the teacher is Quantum Learning with the use of folding cards. The purpose of this study is to find out the increasing activities and learning outcomes of social studies material by using the Quantum learning model on class VIII B students. This research is a classroom action research (CAR) that consist of two cycles, it consist of planning, implementation, observation, and reflection . The results of this research showed that there was an increasing in student learning outcomes from cycle I to cycle II by 74.4, with classical completeness 73.2% to 80 with classical completeness 80%. The results of the activities of students and teachers also increased the first cycle by 70%.  It is increased to 85% in the second cycle, while the activities of teachers in the first cycle of 75%, it is increased to 93.3% in the second cycle. Permasalahan yang muncul dalam pembelajaran IPS di SMP Negeri 1 Batang berawal dari penggunan model dan media pembelajaran yang digunakan guru pada saat pembelajaran. Model saintifik sudah dilaksanakan namun peserta didik tetap diam, tidak berani mengemukakan pendapat. Guru melakukan perbaikan agar peserta didik lebih aktif dan hasil belajar meningkat. Model pembelajaran yang digunakan adalah QuantumLearningdenganberbantuan kartu lipat. Tujuan dari penelitian ini adalah untuk mengetahui peningkatan aktivitas dan hasil belajar materi IPS dengan menggunakan model Quantumlearningpada peserta didik kelas VIII B. Penelitian ini merupakan penelitian tindakan kelas (PTK) yang terdiri dari dua siklus, meliputi perencanaan, pelaksanaan, pengamatan, dan refleksi. Hasil penelitian menunjukkan ada kenaikan hasil belajar peserta didik dari siklus I ke siklus II sebesar 74,4 dengan ketuntasan klasikal 73,2% menjadi 80 dengan ketuntasan klasikal 80%. Hasil aktivitas peserta didik dan guru juga meningkat siklus I sebesar 70% meningkat menjadi 85% pada siklus II, sedangkan aktivitas guru pada siklus I sebesar 75% meningkat menjadi 93,3% pada siklus II.